FUN WAYS SEBAGAI STRATEGI MEMOTIVASI SISWA BELAJAR BAHASA INGGRIS PADA SDN 250 SAPARUA TIMUR - Nikijuluw, Maria Martha (Universitas Pattimura, 2023)
The problem faced by most elementary schools in Maluku, including SDN 250, East Saparua District, Central Maluku Regency, is that they do not receive English lessons at school. However, learning English from a young age is crucial in the current era of globalization. Therefore, community service activities (PkM) carried out through the teaching assistance program also provide English language teaching assistance at the school. This community service activity took place in December 2022 and is directed as